Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 17

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
issued: November, 2022/December, 2022 Number of pages: 12

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Latest Y4Y Quebec Research Outlines What Makes Quebec’s English-Speaking Youth (ESY) a Unique Set of Civic Actors: Quebec’s ESY Speak on the Driving Forces Behind their Civic Engagement. - Winrow, Adrienne (2022)

Learning Disabilities in Quebec : Potential Barriers in French Language Learning for English-Speaking Youth - Alder, Helen (Youth for Youth Québec (Y4Y Québec), 2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Civic Engagement Motivations and Barriers for English-Speaking Quebec Youth - Nykoluk, Brock (2022)
As such, to better understand Québec’s civic land- scape, civic engagement for ESQY ought to receive more scholarly attention. This report aims to help fill this gap by answering the following questions: How do ESQY characterize the motivations behind their civic engagement? How do ESQY characterize the barriers that hinder their civic engagement?

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

The Importance of School Support on the Mental Health of LGBTQIA2S+ Youth in Québec : Policy Brief - Piccolo, Lexie (Youth for Youth Québec (Y4Y Québec), 2022)
LGBTQIA2S+ youth face unique stressors. Québec isfairly inclusive as the province has prohibited discrimination of gender identity and sexual orientation in section 10 of the Québec Charter of Human Rights and Freedoms and urges for sexuality education to be a part of school curriculum. Although the province’s efforts have likely provided some relief to LGBTQIA2S+ Québec youth, reports of bullying and lack of support remain significant, especially in rural regions. Homophobic discrimination is directly and indirectly related to well-being as it can lead to feelings of isolation, which in turn leads to poorer mental health (Blais et al., 2014; Garcia et al., 2020). This is especially true for rural towns across Québec as the lack of queer representation prompts homophobic remarks and leads queer youth to feel alone (Dicaire, 2021). Given the amount of time youth spend in high-school, support within these facilities is essential. Research demonstrates that support systems for LGBTQIA2S+ youth, as well as education about this community within high-schools, may better the mental health of queer youth. In the absence of these tools, their mental health may languish.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 7

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

Sense of Belonging Among English-speaking Youth in Québec : Confronting Isolation Through Digital Community Building - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2022)
Since the onset of Covid-19, community has come to inhabit a digital medium for many of Québec’s English-speaking youth. But what does this mean in concrete terms? How is this linguistic minority using social media, and in what manner are they experiencing this digital shift? Will they want to keep having online events going forward? Our paper observes the digital behavior of young (aged 16-30) English-speaking Québecers from March 2020 until the current moment in the pandemic’s development.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Déclaration sur le refus du gouvernement de la Coalition Avenir Québec de céder sur les dispositions concernant les étudiants des cégeps anglophones - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Statement on Coalition Avenir Québec Government’s Refusal to Budge on Provisions for English-speaking CEGEP Students - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Concert Series to Highlight Talents of Young Musicians Celebrating Local Heritage in the Sonorous Acoustics of St George Anglican Church - Centre for Access to Services in English (CASE) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)
Number of pages: 6

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)
Number of pages: 6

Sondage Youth Pulse Check : Principales conclusions - Community Health and Social Services Network (CHSSN) (2022)

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Booklet for Young Workers : Everything you Need to Know for your First Job - Montérégie West Community Network (MWCN); Educaloi (2022)

Initiative sur la jeunesse et la santé mentale : Rapport d’évaluation - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Sondage Youth Pulse Check : Rapport des résultats du sondage - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Youth Mental Health Initiative : Evaluation Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Annual Report 2021-2022 - Youth for Youth Québec (Y4Y Québec) (2022)